'This feels like a whole new thing': a case study of a new LGBTQ-affirming school and its role in developing 'inclusions'. Issue 12 (2nd December 2018) - Hope, Max A.; Hall, Joseph J.
ABSTRACT: The notion of inclusive education has multiple meanings and the precise definition remains contested. In particular, the debate rages as to whether it is appropriate for some schools to offer specialised provision to particular cohorts of students rather than to educate everyone within a common school. This manuscript foregrounds rich empirical data from students, parents and educators at Pride School Atlanta, described as 'the South's first school for LGBTQ students', a new small, democratic, private school with the explicit intention of creating a 'thriving space' for 'gay, straight, queer, gender-queer' children, young people and families; a space that moves 'beyond safety'. By drawing on Dyson's [2012. 'Inclusion and Inclusions: Theories and Discourses in Inclusive Education.' In World Yearbook of Education 1999: Inclusive Education, edited by H. Daniels and P. Garner. Oxon: Routledge] work on 'inclusions' and moving away from the simple binary of what is inclusive/exclusive, this manuscript addresses the question of whether a school, which offers specialised provision to a small group of students, can play a role in inclusive education. It argues that this model of schooling, described by one student as 'a whole new thing' offers opportunities for presence, participation and achievement, recognition and achievement.